Determinantes da especialização para os municípios cearenses - Santos, Luiz Antonio Alves dos (2008)
This study analyzes agriculture efficiency and productivity in municipal districts in Ceará Brazilian State. The objective is to identify comparative advantage’s determinants for each municipal district`s production of specific products, what would indicate that product specialization could be a feasible road for the development of their economical potentialities. In order to make this analysis, it was considered both historical and more recent aspects, as well as the evolution of agriculture in Ceará State. The analysis; which was based on studies, projects and census reports from previous years; focuses on the variables that will help the political decision behavior. About the empiric analysis, it was calculated the comparative advantages and ran a econometric model to evaluate their determinants. At last, the present study could serve as model for decision-makers analysis about comparative advantages specialization.